Caracterização da função e morte de neutrófilos em mulheres pré-diabéticas e diabéticas: modulação pela suplementação com ômega 3 - Almeida, Mariana Mendes de (2019)
Diabetes mellitus (DM) is a growing problem worldwide. Diabetic patients have altered neutrophilic function associated with a state of chronic inflammation and reduced healing capacity. GA can modulate neutrophil function and death and thus alter the inflammatory response. Omega-3 polyunsaturated GA supplementation, such as eicosapentaenoic (EPA) and docosahexaenoic (DHA), has been used to control infection in autoimmune diseases and is useful in reducing the risk of atherosclerosis and cardiovascular disease. However, the effect of omega 3 supplementation on neutrophils in pre-diabetic and diabetic women remains the best elucidated one. The aim of this study was to characterize the effect of diabetes on neutrophil function in control (glycemia≤100mg / dL), prediabetic (glycemia ≥125mg / dL) and diabetic (glycemia ≤126mg/ dL) women. Omega-3 supplementation in neutrophil function and death in these groups of women. A total of 122 women over 40 years old participated in this study. To determine the effect of pre-diabetes and diabetes on neutrophil function, the volunteers were divided into 3 groups: 1) control, 2) pre-diabetic and 3) diabetic. Subsequently, the effect of omega 3 supplementation was evaluated, for example, women were subdivided into 6 groups 1-) supplemented with soy lecithin (placebo), 2-) supplemented with pre-diabetic omega 3, 3-) supplemented with soy lecithin; 4-) pre-diabetic group supplemented with omega 3; 5-) diabetic supplement group with soy lecithin; 6-) omega-3 diabetic supplement group. High omega with a daily dose equivalent to 1.95 g / day was used or supplemented. Supplementation was performed by the double-blind method and evaluations were used before and after 3 months of supplementation. Neutrophils were submitted to the bloodstream and were performed: adhesion molecule expression (CD54 and CD62L), phagocytosis, production of reactive oxygen species (ROS) and cytokines, cell membrane integrity, DNA fragmentation and mitochondrial membrane polarity. In the first part of the study, pre-diabetic and diabetic groups were observed, with a higher percentage of overweight women than the control group. Neutrophils from diabetic volunteers express less CD54 (ICAM), do not alter the production of ROS after stimulation with LPS and observe a mitochondrial membrane depolarization. After omega 3 supplementation, there was an increase in CD62L expression and a reduction in CD54 in the three reference groups. ROS production by stimulated neutrophils was inhibited in the control and pre-diabetic group. The diabetic group remained unresponsive to the stimulus. Neutrophils without lipopolysaccharide stimulation (LPS) had the production of proinflammatory cytokines (TNFα, IL1β and IL-6) inhibited after omega 3 supplementation. However, supplementation induced cytokine production after neutrophil use with LPS neutrophil death parameters were not altered by supplementation. Soy lecithin supplementation led to similar effects to omega 3 on neutrophil function. We conclude that omega 3 supplementation had an anti-inflammatory effect on the neutrophil function of pre-diabetic and diabetic women, in addition to becoming the most responsive neutrophils, stimulating the production of proinflammatory cytokines. These effects help control the chronic inflammatory response in diabetic patients.